Values of “alternative food initiatives” as expressions of “embeddedness”: A comparative analysis in different national contexts - Stotten, Rike; Brunner, Anna-Maria; Faltmann, Nora Katharina; Froning, Paul; Pixová, Michaela; Plank, Christina (The International Journal of Sociology of Agriculture and Food, 2025)
Values are essential leverage points in the pursuit of sustainability transformations, especially within food systems. In agrifood studies, they are often linked to various forms of alterity relating to food and food systems, which we broadly conceptualize as “alternative food initiatives” (AFIs). This paper explores the role of values within AFIs by enriching Holloway et al.’s (2007) heuristic analytical framework with the concept of “embeddedness” to offer a comparative analysis of how AFIs reconfigure food production, distribution, and consumption through values-based practices. The paper’s analysis focuses on four key dimensions of embeddedness: social, economic, ecological, and spatial. Examining nine case studies across three countries (Switzerland, Czechia, and Argentina) using a qualitative approach, we find that values are neither universal nor neutral; instead, they are shaped by local contexts, influenced by power dynamics, institutional settings, and cultural norms. The paper further finds that the contributions and impacts of values are more diverse than binary understandings of “alternativeness” would suggest, underlining the importance of values for transformations toward sustainable food systems. This research contributes to agrifood studies by illuminating the role of values as leverage points for sustainability, underscoring the importance of contextualized, value-driven approaches in advancing food system transformation.